LARVAL BREEDING HABITATS OF AEDES MOSQUITOES IN VILLAGES AROUND RUBBER PLANTATIONS OF KANYAKUMARI DISTRICT, SOUTH INDIA - Sony X. Vincent1* and Grace Marin2, (Chelonian Research Foundation, 2023)
Aedes mosquitoes transmits virus that cause dengue, chikungunya, west Nile, filariasis and zika diseases. Both Aedes aegypti and Aedes albopictus are responsible for dengue transmission in Kanyakumari district. Aedes albopictus are found abundant in rural areas and Aedes aegypti are abundant in urban areas. These mosquitoes are container breeders and they usually breed in buckets, drums, plastic containers, used tires, mud pots, discarded containers, coconut shells, etc. The larval surveys were done in villages Vadakkanadu and Poovancode which are surrounded by rubber plantations. In Kanyakumari district both rubber and coconut are the major cash crops. In the rubber plantations, coconut shells and plastic cups are used to collect latex from the rubber trees. Here the major sources of larval breeding are rubber tapping cups, coconut shells, plastic buckets, aluminum dishes, glass bottles, overhead tanks and drums, tin cans, etc. The larval surveillance indicators revealed a high risk of dengue outbreak. Knowledge of the breeding habitats and sources in different ecosystem help us to implement appropriate control measures though larval control. Elimination of the mosquito breeding sources by removing collected waters in and around the houses and educating the people are important tools for dengue control. Keywords: Aedes mosquitoes, rubber plantations, breeding sources, HI, CI, BI